Determinants of provider preferences for utilisation of oral health care services in Uganda : A Rural-Urban comparison - Mbaziira, Annette Nannyonjo (Department of Public Health and Family Medicine, 2024)
The demand for health care has been addressed by many researchers in health economics, which is indicative of the important role it plays in the assessment of health service provision and utilisation. However, studies on demand for oral health care are limited, especially in the developing country context. Determining the factors that influence the utilisation of oral health care services and their effect on choice of oral health care providers is instrumental in evaluating a government's commitment to addressing the barriers that impede the provision of equitable health care services. Quantitative and qualitative methods of collecting and analysing data were used. An analytical cross-sectional study was employed to examine the demand for oral health care in rural and urban districts of Uganda. It distinguished between determinants of individuals' choice of oral health care providers in both the public and private sector. Interviewer administered questionnaires were completed by 493 patients from five different districts. The qualitative part combined focus group discussions and in-depth interviews of key informants within the selected districts. The quality of oral health care was found to have a significant effect on demand for health care. The definition of quality in this study includes the availability of drugs, the availability of providers, preferably with a good attitude towards their patients, and a good facility environment. The cost of health care did not have as much an effect on the demand for oral health care as had been expected. Cost issues mainly included factors such as payments at the facilities, consultation fees and informal fees. Other determinants include the distance between the facility and the patient's home, and the severity of the patient's oral health condition. Socio-economic and demographic factors, namely age, gender, education and income, were also assessed. The study recommends that more zealous oral health promoting programmes be conducted and that these should involve dentists disclosing more oral health information to their patients during and after treatment. The greater part of the population has poor access to oral health care services, and thus the study advocates that the government makes available more resources for this cause. It also suggests V that pre-payment schemes be made part of the financing mechanisms, especially for the less affluent, so as to enable them to access health facilities when the need arises. This report begins with an overview of the country's background and how the Ugandan oral health care system operates. Chapter Two reviews the existing literature on issues of demand and determinants of choice of health providers, whereas Chapter Three addresses the methods and analyses of the study. Thereafter, the report presents the analyzed study results, giving a brief discussion of these in Chapters Four and Five respectively. Finally, it suggests ways of providing more equitable services, and improving oral health care service provision in the country of Uganda.